Does the investment interest limitation explain the existence of dividends? - Feenberg, Daniel (Journal of Financial Economics, 1981)
Miller and Scholes have shown that under certain conditions the Federal Income Tax taxes dividend income at a rate no higher than the rate on capital gains. Tabulations of actual 1977 tax returns show that the special circumstances under which this can occur apply to recipients of two and one half percent of dividend income and that no dominant role may therefore be ascribed to their hypothesis in the determination of corporate dividend policy.